(untitled) (Bangladesh Journal of Child Health, 2021)
Background: Sepsis in neonates by resistant strains remains a significant cause of mortality and morbidity in developing countries. This study attempted to find out the organisms responsible for early onset sepsis (EOS) and late onset sepsis (LOS) and determine their antimicrobial sensitivity pattern. Materials & Methods: This prospective observational single centre study was conducted on 1000 neonates during January to September 2018, that were investigated for rule out sepsis, at the Neonatal Intensive Care Unit of Ad-din Medical College Hospital, Dhaka. Results: Fifty-four neonates were found with culture proven sepsis.Coagulase-negative Staphylococci (CONS) (68.42%)was the commonest and followed by Acinetobacter (18.42%) were found on culture isolates in EOS. In LOS, CONS (75%) is the most predominant organism. Among the gram negative Acinetobacter (50%) was the most prevalent bacteria followed by E.coli (28.57%). None of the gram positive isolates were sensitive to Amikacin. Majority of the gram positive showed susceptibilities to Vancomycin (83%) and Linezolid (78%). Among gram negative isolates 93% were sensitive to Colistin, 63% to Gentamicin & 54% to Levofloxacin. Conclusion: Present study indicated that gram positive species especially CONS continue to be the predominant causative organism in both EOS and LOS and followed by Acinetobacter and E. coli in gram negative species. Bangladesh J Child Health 2020; VOL 44 (3) :133-138